Gestión pedagógica intercultural de los docentes del área de comunicación en seis instituciones educativas públicas de secundaria del distrito de San Juan, Iquitos 2023 - Ramos Cardozo, Angie Fiorella (2025)
Diagnosing the intercultural management of teachers in the area of communication in six public secondary educational institutions in the district of San Juan-Iquitos 2023 was the purpose of the investigation. We worked with 56 appointed and hired teachers from six educational institutions; the information was collected through a questionnaire that was validated by three experts. The analysis of intercultural pedagogical management reflects that 63% of teachers reach a medium level, 30.3% a high level, and 6.7% a low level. The research made it possible to diagnose that the intercultural pedagogical management of teachers in the communication area in the evaluated institutions is mostly at a medium level.